Marshall Yardım Planı’nın Türkiye üzerindeki etkileri (1948-1954) - Özkan, Nilgün (My University, 2004)
In my thesis study which covers the affects of Marshall Benefit Plan on Turkey between the years 1948 and 1954, economical and social approaches of the ruling parties and the governments during this period has been tried to be evaluated. Economical and social changes in the country because of the aids started to be given in 1948 given according to the agreement signed in 1947, were explained in a historical approach, the reasons why Turkey started to get loans while it was getting aids and supports, were discussed investigating the applied economical policies, liberalism was discussed if it is the right way to choose, abandoning the state socialism. The main reasons of Marshall Benefit Period that came up with Truman doctrine were deliberated, new formation and understanding following the second world war, approaching especially from Turkey's foreign policies, were discussed together with parallel and opposite applications of CHP and DP governments. Economical policies of both parties have been examined, especially the right and wrong applications of DP were evaluated in a non-partisan look while DP was accused of bowing to the will of USA. Turkey has a big strategic importance. USA and USSR have always shown interest to Turkey. The interest of these two countries has been examined, foreign policy approaches that changed after the Benefit Plan has been evaluated also in this point of view.

1948-1954 yılları arasında Marshall Yardım Planı'nın Türkiye üzerindeki etkilerini kapsayan tez çalışmamda, bu dönem arasında iş başında olan parti ve hükümetlerin ekonomik ve toplumsal yaklaşımları ele alınmaya çalışılmıştır. 1947 yılında imzalanan ve 1948 yılından itibaren Türkiye Cumhuriyeti'ne verilmeye başlanan yardımların ülkede ne gibi ekonomik ve sosyal değişimlere yol açtığı, tarihsel yaklaşım içinde anlatılmış, Türkiye'nin yardım alırken daha sonra neden borç almaya başladığının nedenleri, uygulanan ekonomi politikaları incelenerek ele alınmış, liberalizmin devletçi politikalar terk edilerek seçilen yolun doğru bir yol olup olmadığı tartışılmıştır. Truman Doktrini ile ortaya çıkan yardım sürecinin ana nedenleri üzerinde durularak, II. Dünya Savaşı sonrasında değişen dünya ve oluşan yeni anlayış, Türkiye'nin özellikle dış politika anlaşışı çerçevesinde yaklaşılarak CHP ve DP hükümetlerinin bu konuda paralellikleri ve zıtlıkları ele alınmaya çalışılmıştır. Her iki partinin ekonomik politikaları incelenerek özellikle teslimiyetçilikle suçlanan Demokrat Parti'nin doğruları ve yanlışlarının tarafsız olarak ortaya konulması amaçlanmıştır. Türkiye Cumhuriyeti'nin büyük stratejik öneme sahip bir konumda olması nedeniyle, ABD ve SSCB'nin ülkemizle ilgilenmesi incelenmiş, yardımlar sonrası değişen dış politika yaklaşımları yine bu açılardan ele alınmıştır.
Keywords: Çok taraflı işbirliği; Ekonomi; Ekonomi_Türkiye; Uluslararası ekonomi